Terapia intensiva na graduação médica: nova abordagem, antigas reflexões - MORAES, Ana Paula Pierre de (2003)
This is an analysis of the contribution of the Intensive Care education to the Medical School, and to the undergraduate medical students at the Federal University of Maranhão, Brazil. Used as reference was the National Curriculum Directive of Medical Education, promulgated in October of 2001; the Curricular Structure of Medical Program of the Federal University of Maranhão; and the research of a worldwide literature on Intensive Care. The study was executed based on the methodology of quality research in a case study. Used as scenario was the Federal University of Maranhão that recently has included Intensive Care training in it's program directed at graduate students in their last year of study. Semi-structural interview was conducted with the sixth year graduate student and the teachers of that University concerning their opinions about the interest and utility of the Intensive Therapy Program to the medical education, the current model of education in the care of the critical patient, as well as their perception of their experience with those patients. It is realized that the interest for broaching subject of Intensive Therapy is great in the medical education and it comes from a web of factors that has its beginning in the curiosity of knowing and establishing approaches to the critical patients, something that they believe it is necessary to all doctors. In the attempt to know the model of education used in the initial care of the seriously ill patient, discussed were issues related to the medical practice and the interdisciplinary approaches to the medical education. It is identified that experiencing together in the ICU; awaken, among the medical students, reflexes regarding the technical and human aspects of this profession. The students who participate as a trainee in the ICU live a diverse experience of the medical being. They turn to physiopathology, therapeutics, and multidisciplinary approaches, exchanging communication between the patients and/or their family with themselves, self limitation, facing and having contact with death. It is realized that, in this way, the period of training in this clinic assists in a medical formation that is more generalized, humanist, critical and reflexive, as proposed by the National Curriculum Directive lines.